On Robust Environmental Quality Indices - Khamis, Azme; Abdullah, Mokhtar (Universiti Putra Malaysia Press, 2004)
This paper discusses a formulation of new environmental quality indices, which can be used for monitoring environmental as well as meteorological parameters. The formulation of the indices is based on conventional and robust principal component analysis, which gives the linear combination of environmental parameters. Comparisons are made between the conventional principal component analysis (PCA) indices and robust principal component analysis (RPCA) indices. The results show that the RPCA gave a better alternative linear combination. A numerical example on air quality was used to illustrate the application of the robust environmental indices.